Pendampingan Bacaan Al Quran bagi Anak – Anak Remaja Asrama Sekolah Thamstam Wittya di Pondok Satae, Narathiwat, Thailand Selatan - Nurdin Nurdin (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
This study aims to improve the ability to read, memorise and understand the Qur'an among children and adolescents at Thamstamp Wittya boarding school, Pondok Satae, Narathiwat, Southern Thailand. Running from 5 July 2023 to 3 September 2023, the programme involved 19 students with activities held twice a day after dawn and evening prayers. The methods used included the delivery of tajweed materials, Qur'an recitation practice using the sorogan method, and short surah memorisation assignments. The tajweed materials covered the laws of nun sukun and tanwin, waqof signs, and qolqolah. This approach aims to improve reading techniques, understanding of tajweed, and memorisation of surahs. Initial results show that most students have difficulties in recitation techniques and memorisation, but with intensive assistance, significant improvements in the ability to read and understand the Qur'an are expected, in line with spiritual improvement and Islamic religious education.